Effect of blood loss during caesarean section on coagulation parameters. Issue 202 (June 2021) - Wasserloos, A.; Thomassen, M.C.L.G.D.; Costa, S.D.; Zenclussen, A.; Tchaikovski, V.; Hackeng, T.M.; Stickeler, E.; Tchaikovski, S.N.
Abstract: Introduction: Venous thrombosis is the leading cause of pregnancy-related maternal morbidity and mortality. The thrombosis risk is increased by caesarean section and blood loss, though underlying mechanisms of these prothrombotic changes remain unknown. Materials and methods: This prospective study recruited 50 pregnant women at term undergoing elective caesarean section at University Hospital Magdeburg, Germany. Blood loss during surgery was correlated with the changes in total protein S, full length TFPI (TFPIfl ), prothrombin, the endogenous thrombin potential (ETP) and resistance to activated protein C (APCsr) determined via calibrated automated thrombography. Results: Mean blood loss was 506 ml (95%CI: 456 to 557 ml). Total protein S was 0.63 (95%CI: 0.60 to 0.67) U/ml preoperatively, decreased by 14.8% after caesarean section and almost normalised five days later. TFPIfl was 0.47 (95%CI: 0.41 to 0.53) U/ml before, remained unchanged immediately after and increased by 11.5% five days after surgery. Prothormbin was 1.10 (95%CI: 1.03 to 1.16) U/ml preoperatively, reduced by 10.4% immediately after and increased again five days after caesarean section, exceeding the preoperative values by 4.4% (−0.7 to 9.6). The ETP decreased by 3.9%, whereas the APCsr increased by 37.0% immediately after caesarean section. The changes in total protein S, prothrombin, thrombin generation and APC resistance showed a trend to be more pronounced in the subgroups with higher blood loss. Discussion: Moderate blood loss during caesarean section hardly reduces thrombin generation but aggravates pregnancy-induced APC resistance and combined deficiency of TFPI and protein S, which can account for the increased thrombosis risk in early puerperium. Highlights: Peripartal blood loss results in a simultaneous deficiency of anticoagulant proteins and increases APC resistance. The ETP marginally decreases after a moderate blood loss during caesarean section. Normalisation of various coagulation proteins postpartum follows different patterns. Combined deficiency of anticoagulants and APC resistance can contribute the thrombosis risk after postpartum haemorrhage.